Study on Importance of Environmental Factors on Wheat Productivity - Nandal, Ritu; Kumari, Seema (Innovative Research Thoughts, 2018)
The plant growth and production mechanism is inhibited by abiotic stresses, and as a result, crop yield is decreased. Plants are usually subject to one or two or several abiotic stresses in the region. Crops typically exposed to essential abiotic stresses include drought, high temperature, salt deficiency, and nutrient deficiency. Stresses that are encountered by many plants affect their water status in common. The amount of water available has a significant effect on how climate change can affect areas around the globe (Kurukulasuriya, 2003). Drought, high and low temperature, and high salinity both cause the plants to respond in a peculiar way, with differing susceptibility and reaction. Plants that are affected by water stress show reduced growth and productivity. Changes in rainfall, temperature, and elevated ambient CO2 concentration have the greatest effect on plants, in general. While there is a lack of studies regarding the combined impact of variations in precipitation, temperature, and atmospheric CO2 concentration on wheat yield, there is some available evidence regarding the effects of each shift on wheat yield. Research suggests that drought is the most influential when it comes to minimal rainfall (Trethowan and Pfeiffer, 1999).